Technology entrepreneurship in healthcare: Challenges and opportunities for value creation - Ignat Kulkov; Maria Ivanova-Gongne; Alberto Bertello; Hannu Makkonen; Julia Kulkova; Rene Rohrbeck; Alberto Ferraris (Journal of Innovation & Knowledge (JIK), 2023)
The healthcare industry is nowadays increasingly forced to adapt to new fast-paced changes, despite its conservatism. Indeed, the number of new technology entrepreneurs and technology value is increasing. In this study, we use modern literature and illustrative cases to identify patterns of technological value creation in the healthcare industry with the purpose to form an understanding of the challenges and opportunities for technology entrepreneurs. Hence, we propose a new challenges-opportunities framework for understanding technology entrepreneurship (i.e., technology innovation, technology proactivity, and technology risk-taking) as a foundation for value creation concerning the needs of patients, medical personnel and hospitals, and the whole industry. We also end the article by outlining practical implications at the micro-level (i.e., patient advocacy and technology-enabled engagement strategies), meso-level (i.e., digital health solutions and motivation for collaboration), and macro-level (i.e., trust building and infrastructure).
Keywords: 650; Entrepreneurship; Healthcare; Technology; Value creation